Analysis of Corporate Governance and Bank Performance: Empirical Evidence From Malaysian Banking Industry - Nazaria, Md Aris; Suzila, Mohamed Yusof; Lim, Jia Wen (Macrothink Institute, 2019)
Various theories and empirical studies have been applied and proposed to establish and explain how corporate governance practices are related to banks financial performance. This study concerns the relationship between corporate governance variables and bank performance in Malaysia. The data collected and analysed in this research is from quarter one year 2011 to quarter four year 2016. Various determinants have been identified namely return on equity(ROE) for bank performance measurement, CEO duality, board size, and board gender for corporate governance. Control variables are bank size and bank leverage. The methodologies adopted in this research includes descriptive analysis, correlation analysis, Pooled Ordinary Least Square (OLS) regression, Diagnostic Tests (Jarque-Bera Normality Test, Wooldridge Test and Variance Inflation Factor), Breusch-Pagan (BP) Lagrange Multiplier test, and Hausman test. In this study, the findings indicate that strong board composition and bank leverage were experience better performance.